The Prevalence of Culture Change Practice in US Nursing Homes: Findings From a 2016/2017 Nationwide Survey. Issue 12 (December 2018) - Miller, Susan C.; Schwartz, Margot L.; Lima, Julie C.; Shield, Renée R.; Tyler, Denise A.; Berridge, Clara W.; Gozalo, Pedro L.; Lepore, Michael J.; Clark, Melissa A.
Abstract : Background and Objectives: Given the dynamic nursing home (NH) industry and evolving regulatory environment, depiction of contemporary NH culture-change (person/resident-centered) care practice is of interest. Thus, we aimed to portray the 2016/2017 prevalence of NH culture change-related processes and structures and to identify factors associated with greater practice prevalence. Research Design and Methods: We administered a nationwide survey to 2142 NH Administrators at NHs previously responding to a 2009/2010 survey. Seventy-four percent of administrators (1583) responded (with no detectable nonresponse bias) enabling us to generalize (weighted) findings to US NHs. From responses, we created index scores for practice domains of resident-centered care, staff empowerment, physical environment, leadership, and family and community engagement. Facility-level covariate data came from the survey and the Certification and Survey Provider Enhanced Reporting system. Ordered logistic regression identified the factors associated with higher index scores. Results: Eighty-eight percent of administrators reported some facility-level involvement in NH culture change, with higher reported involvement consistently associated with higher domain index scores. NHs performed the best (82.6/100 weighted points) on the standardized resident-centered care practices index, and had the lowest scores (54.8) on the family and community engagement index. Multivariable results indicate higher index scores in NHs with higher leadership scores and in states having Medicaid pay-for-performance with culture change-related quality measures. Conclusions: The relatively higher resident-centered care scores (compared with other domain scores) suggest an emphasis on person-centered care in many US NHs. Findings also support pay-for-performance as a potential mechanism to incentivize preferred NH practice. Abstract : Supplemental Digital Content is available in the text.